PENERAPAN MERCHANDISING PADA CONVENIENCE STORES DI TOKO BERJEJARING - HERMANTO, HANDOKO (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The phenomenon of emergence of various types of convenience stores currently provide its own color in competition at the retail stores type category, this makes the competition as a venue where convenience stores in search for ways to strengthen their position in the retail market, therefore increasing merchandising as a medium in effectiveness in the stores should be focused according to the circumstances and market conditions. Merchandising is the heart of the retail business. Merchandising in the present context should be viewed not merely as an internal process, but rather as a series of efforts in penediaan retailers and distribution of goods or services from the manufacture or distributor to consumers not only in accordance with the level of need, but rather a collaborative action simultaneously with the supplier in a consumer driven supply chain and category management. In order to increase the effectiveness of merchandising merchandising needs effective management, so that the process can be run with neatly applied and in accordance with the expected goals include procurement, codification processes and information systems, the distribution of goods, and goods handling process.